BEDHAYA BENGAWAN KARYA DJAROT BUDIDARSONO MENGANDUNG PENDIDIKAN KARAKTER BAGI MASYARAKAT JAWA - Sawitri Sawitri; Bani Sudardi; Wakid Abdullah; Nyoman Chaya (Jurnal Pendidikan Ilmu Sosial, 2017)
Bedhaya Bengawan is a dance work performed by nine dancers created by a choreographer named Djarot Budidarsono. Bedhaya Bengawan was created in 2010 performed in Wisma Seni Surakarta, Taman Budaya Surakarta Jawa Tengah (Surakarta Cultural Park of Central Java). The dance work was used as a means of delivering message to the spectators, art observers and community. The theme was adjusted with the artist/choreographer’s idea and creativity. Bedhaya Bengawan is a product inspired by the choreographer living around Bengawan Solo River. River water flows into the river for irrigation purpose; adequate water will yield abundant crops. The farmers express their gratitude to Dewi Sri for the abundant crop. In addition, in this nature, there should be integration between water, soil, wind and sun. The values delivered through Bedhaya Bengawan contain character education for the students including: gratitude to the Only One God, belief in the power of Dewi Sri with any rites as the reward to the abundant rice production, reminder that there should be balance between macrocosm and microcosm. Other character educations include: Manunggaling Kawula Gusti (uniting with God), Sangkan Paraning Dumadi (the origin of human beings and to which [Sang Yang Widi] they will return later). The character education above leads the students to have religious ritual awareness to appreciate nature, to believe in God and to be aware that there is a supreme power creating and nullifying human beings. The secular short life should be filled in with good things. Gratitude should always be expressed to God in order to be blessed. The students are expected to imitate what is included into bedhaya bengawan dance work and to apply it in their daily life.